FINANCIAL GOVERNANCE COUNSELING TO MSMEs IN TEMPO VILLAGE, WEST LOMBOK REGENCY - Syarifah Massuki Fitri; Muhammad Syukri; Suandi; Luh Utami; Widiya Pratiwi; Yusrin Helmi; Anak Agung Widiani Dewi; Ilham Khalid (khidmatan, 2023)
Understanding the financial management and governance of micro, small, and medium enterprises is needed so that micro, small, and medium enterprises can develop and obtain information quickly and accurately for decision-making. Understanding the financial management of Micro, Small, and Medium Enterprises involves traders in Tempos Village, including traders of traditional Lombok snacks. This community service activity aims to improve understanding of the financial management of micro, small, and medium enterprises. Apart from that, if financial records are carried out well, they can produce the correct information for decision-making and solve problems for business actors. With this outreach, the activity participants' awareness level will become more motivated. It will no longer be afraid of seeking capital in the banking and non-banking sectors, which is inherent in business actors. The method of counseling and knowledge about financial governance is carried out by training participants to make simple financial reports. By implementing this program, participants are expected to be able to apply and be able to make simple financial reports that can be used to apply capital to financial institutions.